Influence Of Indian Tv Reality Shows On The Individual Behaviour Of Audience (Students And Faculty Members Of Chandigarh University): A Case Study Of Bigg Boss (Hindi) - Kaur, Dr. Kamaljeet (The journal of contemporary issues in business and government, 2021)
Reality shows are very popular amongst Indian Audience these days. Reality show is a television programme in which ordinary people or participants are filmed continuously. These programmes are totally entertainment based. Bigg Boss, KBC, Indian Idol, Splitsvilla and Super Dancer are the popular Indian TV Reality Shows. But our research paper will focus on Bigg Boss only. The major objective of the paper is to identify the influence of Indian TV Reality Shows on the individual behaviour of the Audience. The research tool will be telephonic Interview of the audience. Audience belongs to Chandigarh University only.